1975
DOI: 10.1530/jrf.0.0430067
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Observations on the Lipid Changes in Rat Corpora Lutea During Various Reproductive States After Treatment With Exogenous Hormones

Abstract: Lipid changes were studied histochemically in rat CL during the oestrous cycle, pregnancy and lactation after treatment with oestradiol benzoate (EB), LH and prolactin. A single injection of 50 mug EB given on any day during the first half of the oestrous cycle, pregnancy and lactation caused a heavy accumulation of lipid droplets, which consisted mainly of cholesterol and/or its esters, triglycerides and some phospholipids. If the treatment with EB was followed by a single injection of 20 i.u. prolactin, drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Their experiments, however, did not eliminate the possibility of stimula¬ tion of progesterone production in the rat CL by prolactin. It has been shown that LH and prolactin act synergistically to regulate the metabolism of choles¬ terol-and triglyceride-containing lipid droplets in the rat CL (Guraya, 1975b), but this does not seem to be true for the interstitial tissue which responds mainly to LH only. It is well established that the depletion of cholesterol-containing lipid drop¬ lets from the interstitial tissue of the rabbit ovary in response to both endo¬ genous and exogenous LH is related to the production of progestins.…”
mentioning
confidence: 98%
“…Their experiments, however, did not eliminate the possibility of stimula¬ tion of progesterone production in the rat CL by prolactin. It has been shown that LH and prolactin act synergistically to regulate the metabolism of choles¬ terol-and triglyceride-containing lipid droplets in the rat CL (Guraya, 1975b), but this does not seem to be true for the interstitial tissue which responds mainly to LH only. It is well established that the depletion of cholesterol-containing lipid drop¬ lets from the interstitial tissue of the rabbit ovary in response to both endo¬ genous and exogenous LH is related to the production of progestins.…”
mentioning
confidence: 98%
“…1975) καί έλαττοΰνται μόνον κατά τό τέλος αυτής. Ίστοχημικαί καί βιοχημικαί μελέται κατέληξαν δτι ή LH καί ή προλακτίνη ρυθμίζουν τόν μεταβολισμόν της χοληστερόλης καί τών άλλων λιπιδίων εντός τών κυττάρων τών ποντικών(Guraya 1975).AL διαταραχαί τοϋ μεταβολισμού των λιπιδίων καί των υδατανθράκων επιδρούν εις τήν πρόκλησιν ατυχημάτων της εμ βρυϊκής αναπτύξεως. *Υπερλιπαιμικαί καταστάσεις πού προεκλήθησαν διά τοϋ Triton Wr 1339 έδειξαν περισσοτέρας βλάβας έκ της υπογλυκαιμίας, διά τήν έκβασιν της κυήσεως καί τήν άνάπτυξιν τοϋ εμβρύου(Tuchmann Duplessis 1974).…”
unclassified